Finite‐element modelling of frictional behaviour between oesophagus and endoscope. Issue 3 (5th August 2020) - Lin, Chengxiong; Ren, Pan; Li, Wei; Deng, Hengyi; Zhou, Zhongrong
Abstract : The endoscopy is the most direct and effective means for digestive tract diseases. Medical workers can conduct a series of manipulations with the help of endoscope, including checking, removing, stripping the diseased tissue or placing the stent. In order to understand the frictional behaviour at the endoscope–oesophagus interface, the finite‐element model was analysed by Abaqus in this study. Considering the different modelling conditions, the total force due to frictional stress, frictional dissipation and the maximum Mises stress for the whole model were studied. Results showed that with the increasing amplitude, coefficient of friction and decreasing diameter, the total forces due to the frictional stress and the FD increased obviously. It did not present a clear difference with the variable distance for overlapping parts (region L). The positions of maximum Mises stress for the whole model under different conditions mainly focused on the initial part of the region R. The maximum Mises stress between different diameters showed a big difference. The results can provide the basic data for the finite‐element modelling of frictional behaviour of human tissue.